2020
DOI: 10.1186/s12909-020-02176-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Interprofessional education in the medical curriculum: a systematic review of the literature

Abstract: Background: There is agreement among educators and professional bodies that interprofessional education needs to be implemented at the pre-registration level. We performed a systematic review assessing interprofessional learning interventions, measuring attitudes towards interprofessional education and involving pre-registration medical students across all years of medical education. Methods: A systematic literature review was performed using PubMed, PsycINFO, EThOS, EMBASE, PEDro and SCOPUS. Search terms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 62 publications
1
21
0
1
Order By: Relevance
“…Nevertheless, the complexity of teaching for different healthcare disciplines, logistical problems and busy timetables raise issues concerning the introduction of IPE interventions. Current undergraduate literature shows a trend for earlier IPE introduction [5,6], but the optimal timing for the IPE intervention is unclear [7]. IPE interventions can be measured by using validated attitudes scales based on IPE domains.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the complexity of teaching for different healthcare disciplines, logistical problems and busy timetables raise issues concerning the introduction of IPE interventions. Current undergraduate literature shows a trend for earlier IPE introduction [5,6], but the optimal timing for the IPE intervention is unclear [7]. IPE interventions can be measured by using validated attitudes scales based on IPE domains.…”
Section: Introductionmentioning
confidence: 99%
“…IPE is essential for the awakening of healthcare students to the need for collaborative working to enhance patient care (WHO, 2010). Studies have demonstrated a positive attitude by students towards IPE (Berger-Estilita et al, 2020) with some evidence for enhanced patient health outcomes (Oosterom et al, 2019;Shrader et al, 2018). Our study explored MED and SLT student perspectives about their experience following one 3-hour classroom-based IPE workshop that focussed on a complex health condition that both disciplines would manage collaboratively when qualified.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have evaluated the attitudes of healthcare students towards IPE. Berger-Estilita et al (2020) found more than 50% of their included studies demonstrated a significant increase in positive attitudes towards IPE by students following an IPE experience. Findings suggest that following IPE attitudes and perceptions of each other's profession improves (Reeves et al, 2016;Spaulding et al, 2019) with a significant improvement in collaborative knowledge and skills (Reeves et al, 2016) and behaviour (Spaulding et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The revised version of the 19 item RIPLS with four subscales (teamwork and collaboration, negative professional identity, positive professional identity, roles and responsibilities) was chosen, 14 because it is the most widely used scale measuring attitudes towards IPL. 5 The items are scored on a 5-point Likert scale (1 = strongly disagree, 2 = disagree, 3 = undecided, 4 = agree, 5 = strongly agree). Given the reverse scoring of items in subscale two and four, higher scores on each subscale suggest more positive attitudes to IPE.…”
Section: Methodsmentioning
confidence: 99%